2012
DOI: 10.1590/s0102-09352012000500029
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo e respostas fisiológicas de cabritos alimentados com dietas contendo torta de girassol oriunda da produção de biodiesel

Abstract:  RESUMOAvaliou-se o efeito de dieta com torta de girassol, oriunda da produção de biodiesel, sobre o comportamento ingestivo e a resposta fisiológica de 32 cabritos ½ sangue Boer, não castrados, com peso médio inicial de 15,3±3,2kg e idade média de 135 dias. Utilizou-se delineamento inteiramente ao acaso, com quatro tratamentos 0; 8; 16 e 24% de inclusão da torta de girassol e oito repetições. O tempo despendido com ruminação, ócio e mastigação total não foi influenciado pela dieta, e observou-se efeito linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This fact contradicts the expectations because the intake of these components was reduced by the addition of RFO (Table 2). Conversely, Freitas et al (2010) and Agy et al (2012) found that feeding efficiency is influenced by the intake of component nutrition (DM and NDF). However, the effect of RFO levels on feeding efficiency has not been verified by regression analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This fact contradicts the expectations because the intake of these components was reduced by the addition of RFO (Table 2). Conversely, Freitas et al (2010) and Agy et al (2012) found that feeding efficiency is influenced by the intake of component nutrition (DM and NDF). However, the effect of RFO levels on feeding efficiency has not been verified by regression analysis.…”
Section: Resultsmentioning
confidence: 98%
“…These differences may affect intake behavior, which is influenced by the physical structure and the chemical composition of diets (CARVALHO et al, 2004). The study of intake behavior is necessary to evaluate foods and diets, to elucidate problems related to decreased consumption, and to adjust the feeding regime of the animals to maximize production and economic performance (AGY et al, 2012). Intake behavior has been studied with regard to the characteristics of food, rumen motility, alertness and the climatic environment.…”
Section: Introductionmentioning
confidence: 99%